Different Activity of the Biological Axis VEGF-Flt-1 (fms-Like Tyrosine Kinase 1) and CXC Chemokines between Pulmonary Sarcoidosis and Idiopathic Pulmonary Fibrosis: A Bronchoalveolar Lavage Study - Katerina M. Antoniou; Giannoula Soufla; Athanasia Proklou; George Margaritopoulos; Christiana Choulaki; Rena Lymbouridou; Katerina D. Samara; Demetrios A. Spandidos; Nikolaos M. Siafakas (Clinical and Developmental Immunology)
Background. We have previously shown a different local and systemic angiogenic profile of CXC chemokines in Idiopathic Pulmonary Fibrosis (IPF) patients compared to sarcoidosis. In particular, sarcoidosis showed an angiostatic microenvironment, as compared with the angiogenic cytokine milieu seen in IPF. Purpose of the Study. Our aim was to further investigate the aforementioned finding by measuring the expression of different chemokines in granulomatous and fibrotic diseases. We estimated the levels of vascular endothelial growth factor (VEGF) and its high-affinity receptor, Flt-1 (fms-like tyrosine kinase 1), in bronchoalveolar lavage fluid (BALF) of patients with IPF and pulmonary sarcoidosis. We have also investigated the mRNA expression of angiogenetic chemokines' receptors such as CXCR2 and CXCR3 and the biological axis of stromal derived factor-1𝛼 (SDF-1𝛼 or CXCL12𝛼/CXCL12𝛽) and receptor, CXCR4. Methods. We studied prospectively three groups of patients: (i) one group of 18 patients with IPF, (ii) one group of 16 patients with sarcoidosis, and (iii) 10 normal subjects. Results. A statistically significant increase has been detected in VEGF mRNA expression in IPF in comparison with pulmonary sarcoidosis (𝑃=.03). In addition, a significant increase has been measured in CXCL12𝛼 in sarcoidosis in comparison to IPF (𝑃=.02). Moreover, a statistically significant decrease has been found in Flt-1 protein levels in pulmonary sarcoidosis in comparison with IPF (𝑃=.03). A significant increase in VEGF (𝑃=.03) and CXCR4 (𝑃=.03) mRNA levels has been also detected in sarcoidosis' patients when compared with healthy controls. Conclusions. Our data suggest that increased expression of Flt-1 and downregulation of CXCL12𝛼 in IPF may further support the hypothesis of a different angiogenetic profile between fibrotic and granulomatous diseases. However, further studies are needed in order to better investigate these enigmatic diseases.